Quantitative meta-analysis of fMRI and PET studies reveals consistent activation in fronto-striatal-parietal regions and cerebellum during antisaccades and prosaccades - Jamadar, Sharna; Fielding, Joanne; Egan, Gary (Frontiers in Psychology, 2013)
The antisaccade task is a classic task of oculomotor control that requires participants to inhibit a saccade to a target and instead make a voluntary saccade to the mirror opposite location. By comparison, the prosaccade task requires participants to make a visually-guided saccade to the target. These tasks have been studied extensively using behavioral oculomotor, electrophysiological, and neuroimaging in both non-human primates and humans. In humans, the antisaccade task is under active investigation as a potential endophenotype or biomarker for multiple psychiatric and neurological disorders. A large and growing body of literature has used functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) to study the neural correlates of the antisaccade and prosaccade tasks. We present a quantitative meta-analysis of all published voxel-wise fMRI and PET studies (18) of the antisaccade task and show that consistent activation for antisaccades and prosaccades is obtained in a fronto-subcortical-parietal network encompassing frontal and supplementary eye fields (SEFs), thalamus, striatum, and intraparietal cortex. This network is strongly linked to oculomotor control and was activated to a greater extent for antisaccade than prosaccade trials. Antisaccade but not prosaccade trials additionally activated dorsolateral and ventrolateral prefrontal cortices. We also found that a number of additional regions not classically linked to oculomotor control were activated to a greater extent for antisaccade vs. prosaccade trials; these regions are often reported in antisaccade studies but rarely commented upon. While the number of studies eligible to be included in this meta-analysis was small, the results of this systematic review reveal that antisaccade and prosaccade trials consistently activate a distributed network of regions both within and outside the classic definition of the oculomotor network.